Safety of antifibrinolytics in cranial vault reconstructive surgery: a report from the pediatric craniofacial collaborative group. Issue 3 (17th February 2017) - Goobie, Susan M.; Cladis, Franklyn P.; Glover, Chris D.; Huang, Henry; Reddy, Srijaya K.; Fernandez, Allison M.; Zurakowski, David; Gries, Heike; Stricker, Paul A.; ,
Summary: Background: Antifibrinolytic therapy significantly decreases blood loss and transfusion in pediatric cranial vault reconstructive surgery; however, concern regarding the side effects profile limits clinical use. Aims: The aim was to utilize the Pediatric Craniofacial Surgery Perioperative Registry database to identify the safety profile of antifibrinolytic therapy for cranial vault reconstructive surgery by reporting the incidence of adverse events as they relate to exposure to tranexamic acid and aminocaproic acid compared to no exposure to antifibrinolytics. Methods: The database was queried for cases of open cranial vault reconstructive surgery. Less invasive procedures such as neuro‐endoscopic and spring‐mediated cranioplasties were excluded. The outcomes evaluated included any perioperative neurological adverse event including seizures or seizure‐like movements and thromboembolic events. Results: Thirty‐one institutions reported a total of 1638 cases from 2010 to 2015. Total antifibrinolytic administration accounted for 59.5% (tranexamic acid, 36.1% and aminocaproic acid, 23.4%), with 40.5% not receiving any antifibrinolytic. The overall incidence of postoperative seizures or seizure‐like movements was 0.6%. No significant difference was detected in the incidence of postoperative seizures between patients receiving tranexamic acid and those receiving aminocaproic acid [the odds ratio for seizures being 0.34 (95% confidence interval: 0.07–1.85) controlling for American Society of Anesthesia (ASA) physical class] nor in patients receiving antifibrinolytics compared to those not administered antifibrinolytics (the odds ratio for seizures being 1.02 (confidence interval 0.29–3.63) controlling for ASA physical class). One complicated patient in the antifibrinolytic group with a femoral venous catheter had a postoperative deep venous thrombosis. Conclusions: This is the first report of an incidence of postoperative seizures of 0.6% in pediatric cranial vault reconstructive surgery. There was no significant difference in postoperative seizures or seizure‐like events in those patients who received the tranexamic acid or aminocaproic acid vs those that did not. This report provides evidence of the safety profile of antifibrinolytic in children having noncardiac major surgery. Caution should prevail however in using antifibrinolytic in high‐risk patients. Antifibrinolytic dosage regimes should be based on pharmacokinetic data avoiding high doses. Abstract :